2008
DOI: 10.1016/s0301-0546(08)72537-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of ace gene polymorphism in the development of angioedema secondary to angiotensin converting enzyme inhibitors and angiotensin II receptor blockers

Abstract: Our results showed that ACE gene polymorphism has no effect on ACEi or ATRB induced angioedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…In Chinese patients there is evidence that genetic polymorphism is associated with a structural alteration in ACE [19]. However, recent data showed no relationship between ACE gene polymorphism and the occurrence of angioedema with ACE and ARB [20]. One study analyzed the metabolism of endogenous bradikinin (B2 receptor agonist) and its active metabolite, des-Arg9-Bradikinin (B1 receptor agonist) in the presence of an ACE-inhibitor during in vitro contact activation of plasma from hypertensive patients who presented angioedema and these kinetic parameters were compared with those measured in a control group (without angioedema) of hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese patients there is evidence that genetic polymorphism is associated with a structural alteration in ACE [19]. However, recent data showed no relationship between ACE gene polymorphism and the occurrence of angioedema with ACE and ARB [20]. One study analyzed the metabolism of endogenous bradikinin (B2 receptor agonist) and its active metabolite, des-Arg9-Bradikinin (B1 receptor agonist) in the presence of an ACE-inhibitor during in vitro contact activation of plasma from hypertensive patients who presented angioedema and these kinetic parameters were compared with those measured in a control group (without angioedema) of hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…ACEİ'e bağlı gelişen anjioödemde dudaklar, dil, yüz ve üst solunum yolu daha sık etkilenir. Bununla birlikte nadir de olsa intestinal anjioödem gelişimine de neden olabilmektedirler (6). Direk kinin üzerine etkileri olmamasına rağmen ARB de intestinal anjioödemle ilişkili bulunmuştur (7).…”
Section: Discussionunclassified
“…[96][97][98] One of these studies reported a 50% lower ACE activity in ACEi-A cases compared to controls taking the same drug, and independent of the presence of the insertion/deletion variation 98 and, the two other studies failed to replicate this finding. 96,97 No other variants in ACE gene have been studied in association with ACE-A. The only GWAS also did not find any significant associations with variants in this gene.…”
Section: Ace Genementioning
confidence: 99%